Single phase transformerless inverter for grid connected photovoltaic system with reduced leakage current - Janardhan, Gurram; Surendra Babu, N. N. V.; Srinivas, G. N. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Transformerless inverters are of vital importance in the field of grid connected solar photovoltaic systems offering higher efficiency than the conventional one. i.e., using transformer. General grid connected inverters are constituting of transformers requires more area besides the loss in them. Problem. Eliminating transformers can cause leakage current due to the variation of common mode voltage which in turn due to parasitic capacitance effect. Research literature in transformerless inverters has addressed the problems of common mode leakage current issues by offering the study of different inverter topologies like H4, H5, H6 and HERIC etc. utilizing variety of modulation strategies like unipolar, bipolar pulse width modulations. Goal. The paper significantly presents a new transformerless inverter topology, analyzes common mode voltage and leakage current behavior of the system. The simulation is carried out for comparing the leakage current profiles with other transformerless inverter topologies in literature. Novelty. This paper gives an impression of the efficient transformerless inverter for grid connected photovoltaic system. Results. The various inverter topologies full bridge with different pulse width modulation techniques are analyzed and to determine the common mode voltages and leakage currents.

Безтрансформаторні інвертори мають життєво важливе значення в області сонячних фотоелектричних систем, підключених до мережі, та забезпечують більш високу ефективність, ніж звичайні, завдяки трансформатору. Підключені до загальної мережі інвертори, які складаються з трансформаторів, потребують більшої площі через втрати у них. Проблема. Усунення трансформаторів може спричинити струм витоку через зміну синфазної напруги через вплив паразитної ємності. Дослідницька література з безтрансформаторних інверторів присвячена проблемам синфазних струмів витоку, пропонуючи дослідження різних топологій інверторів, таких як H4, H5, H6, HERIC та ін., з використанням різних стратегій модуляції, таких як уніполярна, біполярна широтно-імпульсна. Мета. У статті докладно подано нову топологію безтрансформаторного інвертора, проаналізовано поведінку синфазної напруги та струму витоку в системі. Моделювання проводиться для порівняння профілів струму витоку з іншими топологіями безтрансформаторних інверторів, описаних у літературі. Новизна. Ця стаття містить ефективний безтрансформаторний інвертор для фотоелектричної системи, підключеної до мережі. Результати. Проаналізовано різні топології інверторів з повним мостом та різними методами широтно-імпульсної модуляції, а також визначено синфазну напругу та струми витоку.
Keywords: transformerless inverter; leakage current; photovoltaic system; безтрансформаторний інвертор; струм витоку; фотогальванічна система